Biomarkers of Innate Immunity and Immunological Susceptibility to Viral Infection in Patients with Alcoholic Cirrhosis - Isabel Legaz; Elena Navarro-Noguera; Aurelia Collados-Ros; Jose Miguel Bolarín; Manuel Muro (Biomedicines, 2024)
Background: The harmful effect of alcohol on the immune system may be due to both a direct action of the alcohol or its metabolites on immune cells as an indirect action modifying the different mechanisms of intercellular interaction. The interplay between stimulatory (aKIR) and inhibitory (iKIR) natural killer (NK) cell receptors and their corresponding human leukocyte antigen (HLA) ligands influences the outcome of virus infection. The aim was to analyze the influence of the KIR/HLA pair genetic profile in male alcoholic cirrhosis (AC) patients with and without viral infections to find susceptibility biomarkers that can help establish the risks and prevent viral infections. Methods: A total of 281 male AC patients were analyzed. The sociodemographic characteristics, viral hepatitis C (HCV), hepatitis B (HBV), and cytomegalovirus (CMV) infections were analyzed. Genomic DNA was extracted, and genetic the KIR/HLA profiles were investigated. A total of 6 KIR genes and their corresponding ligands (HLA-C) were analyzed. Patients were grouped into two groups: with and without associated viral infection. Results: A statistically significant increase in the combination of KIR2DL2+/C1C1 was observed in male AC patients with viral infection compared to those without viral infection (45.9% vs. 24.5%, p = 0.021). The analysis of KIR2DL3+/C1+ showed a high frequency comparing healthy controls and male AC patients without virus infection (85% vs. 76.4%; p = 0.026). The analysis of KIR2DL3+/C2C2 frequency showed a statistically significant increase comparing male AC patients without viral infection and healthy controls (23.6% vs. 15%; p = 0.026). Conclusions: The genetic KIR2DL2+/C2C2 profiles may play a significant role in determining the vulnerability of male AC patients to viral infections, providing valuable insights for future research and potential therapeutic interventions.